Understanding rehabilitation and support needs after an episode of delirium: a qualitative thematic analysis of interviews with older people with delirium, family carers and healthcare professionals - S. Raghuraman; E. Richards; A. Mahmoud; S. Morgan-Trimmer; L. Clare; R. Anderson; VA Goodwin; L. Allan (BMC Geriatrics)
Abstract Background Delirium is linked to adverse outcomes in older adults and independently increases the risk of developing or worsening dementia. While most research focuses on acute-phase management, long-term recovery remains poorly understood. This study explores post-discharge trajectories through a qualitative investigation of the perceived home rehabilitation and support needs of older adults following delirium. Methods A thematic analysis approach was used to investigate the perceived home rehabilitation needs of older people who experienced delirium during hospital admission. Semistructured interviews were conducted with 46 key stakeholders (older people − 8, carers − 14, and healthcare professionals − 24). Results Several interconnected themes were identified as potential resources that enable recovery from delirium: (a) social contact and recovery of social lives; (b) the need for information, support, and education; (c) personalisation and personhood; (d) relationship continuity with professional carers; (e) the experience and involvement of carers; and (f) treating the cause and healthy lifestyle. Conclusion This study addresses notable research and practice gaps in the long-term treatment of delirium at home. This knowledge contributes to the development of an evidence-based theory of long-term delirium recovery.